Are powered or manual toothbrushes better for removing dental plaque and treating gingivitis?. Issue 3 (March 2016) - Karnes, Sharon; Bell, Darin
Abstract : Evidence‐Based Answer : Powered toothbrushes, especially the rotation oscillation type, reduce plaque and gingivitis scores in both shortand long‐term studies more than manual toothbrushes. The magnitude of effect is greater with longer use (SOR: C, meta‐analysis of RCTs and individual RCTs, all with disease‐oriented results).